Розробка технології виробництва заготовок періодичного профілю вібраційним волочінням - Шаповал, Олександр Олександрович (НТУ "ХПІ", 2017)
Отримання заготовок періодичного профілю з нікелевих і титанових сплавів є самостійною задачею в загальній проблемі вдосконалення технології виробництва лопаток. Виявлено, що при певних схемах і режимах вібраційного деформування (зокрема, при віброволочінні) спостерігається ефект періодичної зміни діаметра прутка або проволоки по його вісі. Встановлено, що ефект періодичної зміни діаметра прутка або проволоки при віброволочінні пов'язане з фрикційними коливаннями; втратою стійкості при деформації як при виникненні напружень плинності в матеріалі прутка, так і при утворенні "шийки", а також як результат дії сил інерції.

Manufacturing periodic profile bars of nickel and titanium alloys is an independent task in the general problem of improving blade manufacturing technology (sinle-locked, double-locked). It is found that under certain schemes and vibrational deformation modes (in particular, when vibrodrawing) the effect of periodic change of the bar or wire diameter along its axis is observed. It was found that the effect of the periodic variation of the diameter of the rod or wire at vibrovodrawing is associated with friction fluctuations, loss of stability during deformation both during the yield stress in the bar material and the formation of a "neck", and also as a result of the action of the inertia forces. The dependences for determining the conditions of the unstable strain and stabilizing the process of obtaining a periodic profile by controlling the parameters of the vibrodrawing process are obtained. the production of billets of periodic profile from nickel and titanium alloys is an independent task in the general problem of improving the technology of production of blades (single-blade, two-slot). It is advisable to carry out control over the properties of the obtained products by methods of nondestructive testing.
Development of technology of manufacturing of periodic profile bars by vibratory drawing
Keywords: циклічний підпір; вібраційне волочіння; періодичний профіль; формоутворення; інертні сили; поршень; vibration drawing; cyclic support; periodic profile; forming; inert forces; self-unscrewing piston